2004
DOI: 10.1111/j.1365-2494.2004.00436.x
|View full text |Cite
|
Sign up to set email alerts
|

Production performance and meat quality of grazing lambs finished on red clover, lucerne or perennial ryegrass swards

Abstract: Fraser, M. D., Speijers, M. H. M., Theobald, V. J., Fychan, A. R., Jones, R. (2004). Production performance and meat quality of grazing lambs finished on red clover, lucerne or perennial ryegrass swards. Grass and Forage Science, 59, (4), 345-356. Sponsorship: DEFRA / MLCThe combined benefits of a high crude protein concentration, and possible protein protection and growth-promoting properties, make forage legumes potentially attractive as a natural means of increasing liveweight gain and time to slaughter of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
51
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(57 citation statements)
references
References 40 publications
5
51
0
1
Order By: Relevance
“…It would be expected that if the diets containing WGP silages had been formulated to maximize niicrobial protein supply, then improved N efficiency may have been observed. Fraser et al (2004) and Speijers et al (2004) reported a greater forage DMI when either grazed red clover or alfalfa was offered to lambs in comparison with grazed ryegrass with the same effect observed when these forages were ensiled (Speijers et al, 2005). Forage DMI was unaffected by dietary treatment in the current study.…”
Section: N Balancesupporting
confidence: 55%
See 2 more Smart Citations
“…It would be expected that if the diets containing WGP silages had been formulated to maximize niicrobial protein supply, then improved N efficiency may have been observed. Fraser et al (2004) and Speijers et al (2004) reported a greater forage DMI when either grazed red clover or alfalfa was offered to lambs in comparison with grazed ryegrass with the same effect observed when these forages were ensiled (Speijers et al, 2005). Forage DMI was unaffected by dietary treatment in the current study.…”
Section: N Balancesupporting
confidence: 55%
“…The plasma urea concentrations were, however, increased in lambs offered WCP-silagecontaining diets, indicating a potential deficit of rumen fermentable energy and further suggesting that feeding WCP silage in combination with a cereal or a cerealbased forage instead of GS would be beneficial. Fraser et al (2004) and Speijers et al (2004) also reported increased plasma urea concentration in lambs consuming grazed legumes in comparison with ryegrass. A similar effect was observed when the forages were ensiled (Speijers et al, 2005).…”
Section: Plasma Metabolitesmentioning
confidence: 83%
See 1 more Smart Citation
“…A key role in this respect may be ascribed to red clover which is likely to exhibit a strong capacity to stimulate changes in the fatty acid profile owing to, among other things, a high content of polyphenolic oxidase (PPO) that inhibits lipolysis (Dewhurst et al 2003). Studies have shown that inclusion of red clover into the lambs' diet in the form of both green forage (Fraser et al 2004) and silage (Lourenco et al 2007) had a beneficial effect on the fatty …”
mentioning
confidence: 99%
“…A key role in this respect may be ascribed to red clover which is likely to exhibit a strong capacity to stimulate changes in the fatty acid profile owing to, among other things, a high content of polyphenolic oxidase (PPO) that inhibits lipolysis (Dewhurst et al 2003). Studies have shown that inclusion of red clover into the lambs' diet in the form of both green forage (Fraser et al 2004) and silage (Lourenco et al 2007) had a beneficial effect on the fatty acid profile in intramuscular fat, as it increased the contribution of polyunsaturated fatty acids (PUFA) in this fat, including that of conjugated linoleic acid (CLA) cis-9, trans-11 being of high importance in terms of health. Research done by Lourenço et al (2007) suggests that feeding lambs with different silages induces changes in fatty acids metabolism in the rumen that may derive from differences in the extent of PUFAs biohydrogenation.…”
mentioning
confidence: 99%